A Nitrogen‐Doped Porous Carbon Supported Copper Catalyst from a Scalable One‐Step Method for Efficient Carbon Dioxide Electroreduction. Issue 2 (27th December 2022) - Vijayakumar, Amruthalakshmi; Zhao, Yong; Wang, Kezhong; Chao, Yunfeng; Chen, Haiqun; Wang, Caiyun; Wallace, Gordon G.
Abstract: In this work, a scalable one‐step glucose blowing method has been used to prepare a porous N‐doped carbon supported Cu nanoparticles (Cu‐NC) composite catalyst for CO2 electroreduction. This Cu‐NC catalyst demonstrates efficient catalytic activity for CO2 ‐to‐C1 product (CO and formate) conversion, with a high efficiency of 69 % at an overpotential of 590 mV. The excellent catalytic activity is correlated to the structure of this composite and the N‐species (pyridinic and graphitic nitrogen) in the carbonaceous matrix that may promote the CO2 adsorption and subsequent formation of reduction reaction intermediates and products. Abstract : Composite Catalyst for CO2 Electroreduction : A nitrogen‐doped porous carbon supported copper catalyst is produced via an ecofriendly scalable one‐step method for the efficient electrochemical conversion of CO2 to formate and CO.